Dynamic scaffolding solution based on business rules - Carvalho, André Emanuel Cajús de (2020)
There is a wide range of architectures and frameworks used to aid in creating web solutions. Some tools provide templates and mechanisms to hasten this process and which we address as scaffolding. We aim to design a solution that facilitates creating back-end applications, by presenting ways to interact with the database out-of-the-box, giving enclosed mechanisms to perform tasks without the need to produce back-end systems from scratch, creating complete web solutions on the fly. After choosing an appropriate architecture and a framework to build such a tool, we have studied scaffolding solutions and their mechanisms, to understand how to design it and what to include. Subsequently, we establish a scaffolding solution to control databases that provide simple ways to apply business rules. As a result, by using a database or a model, users can generate a project structure without programming skills. The product of our generator it is a system that aims to help with creating and updating data so that its insertion is intuitive and validated, ensuring that it respects and is in line with what the database expects. Our tool also works as the basis for more elaborate solutions, since its structure facilitates adding further business logic. Even though there are similar solutions, it brings a new concept regarding the data interconnection presentation mechanisms, and it holds features that solutions alike do not.